Ilmu Hukum Dalam Pusaran Perkembangan Ilmu Pengetahuan - BAMBANG SUGIRI (Fakultas Hukum Universitas Mulawarman, 2008)
Early development of Law Science as a part of science definitely continues to haveadvanced progression. At certain age, law science idealism has been accompanied withnatural law idealism. At other age, normative-positivist idealism also dominates allthoughts about law. The charming appeal of normative-positivist idealism brings somepeople to regard it as the sole perspective and the underlying characteristic of lawscience. In the midst of recently uproarious science development, normative-positivistmainstream paradigm finally faces a challenge, questioning whether it refers to a soleperspective of law science. Do any other more progressive law perspectives exist withcapability to take law science into a genuine science? In the midst of recent sciencedevelopment, law science seems incapable to deny a fact that it has a susceptibility tothe effect of more developing science.Key words : Ilmu hukum (law science), ilmu pengetahuan (science)